Proteome Profiling of Paulownia Seedlings Infected with Phytoplasma - Cao, Xibing; Fan, Guoqiang; Dong, Yanpeng; Zhao, Zhenli; Deng, Minjie; Wang, Zhe; Liu, Wenshan (Frontiers in Plant Science, 2017)
Phytoplasma is an insect-transmitted pathogen that causes witches’ broom disease in many plants. Paulownia witches’ broom is one of the most destructive diseases threatening Paulownia production. The molecular mechanisms associated with this disease have beeninvestigated by transcriptome and microRNA sequencing, but changes inprotein abundancehave not been investigated with isobaric tags for relative and absolute quantitation. Previous results have shown that methyl methane sulfonate (MMS) can help Paulownia plantlets recover from the symptoms of witches’ broom and reinstate a healthy morphology. In this study, a transcriptomic-assisted proteomic technique was used to analyze the protein changes in phytoplasma-infected Paulownia tomentosa plantlets, phytoplasma-infected plantlets treated with 20 and 60 mgL−1MMS, and healthy plantlets. A total of 2051 proteins were obtained, 879 of which were found to be differentially abundant in pairwise comparisons between the sample groups. Among the differentially abundant proteins, 43 were related to Paulownia witches’ broom diseaseand many of them were annotated to be involved in photosynthesis, drarf symptom, energy production, and cell signal pathways.